1971
DOI: 10.1007/bf02531229
|View full text |Cite
|
Sign up to set email alerts
|

The effect of undernutrition on the development of myelin in the rat central nervous system

Abstract: Newborn rats were segregated into litters of 6 and 22 pups. Undernourished groups were maintained for 21 and 53 days at which time a portion of each group was sacrificed and the remainder refed until 121 days. The amount of myelin isolated from the central nervous system was decreased in nutritionally deprived animals but there was little change in its chemical composition or intereference in the normal chemical maturation of the membrane. The only consistent change was a reduction in phosphatidyl ethanolamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

1974
1974
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 39 publications
(21 reference statements)
4
18
0
Order By: Relevance
“…White matter is largely composed of oligodendrocytes and astroglia along with the axonal processes, whereas grey matter can be considered a region largely made up of neurons and some astrocytes. Since neurons are supposed to reach the postmitotic stage by birth in rat and glial cells, particularly the oligodendrocytes, are known to proliferate postnatally in this species [Brizzee et al, 1963;Vernadakis, 1973;Subba Rao and Shrivastaw, 19791, the present results can be considered to be in full conformity with the "vulnerable period" hypothesis of Dobbing [1972] as well as with the postulations of Winick and co-workers [1968, 19701. Since oligodendrocytes are the cells responsible for myelin synthesis, the present results also substantiate earlier findings on the decreased synthesis and content of myelin as a result of postnatal protein or calorie deficiency [Benton et al, 1966;Chase et al, 1967;Fishman et al, 1971;Nakhasi et al, 1975;Krigman and Hogan, 1976;Wiggins et al, 1976;Figlewicz et al, 1978;Kim and Pleasure, 19781. However, the present results are in disagreement with those of Bass et a1 [1970], who did not find any decrease in DNA content of the white matter region of rat brain in response to weanling undernutrition.…”
Section: Discussionsupporting
confidence: 93%
“…White matter is largely composed of oligodendrocytes and astroglia along with the axonal processes, whereas grey matter can be considered a region largely made up of neurons and some astrocytes. Since neurons are supposed to reach the postmitotic stage by birth in rat and glial cells, particularly the oligodendrocytes, are known to proliferate postnatally in this species [Brizzee et al, 1963;Vernadakis, 1973;Subba Rao and Shrivastaw, 19791, the present results can be considered to be in full conformity with the "vulnerable period" hypothesis of Dobbing [1972] as well as with the postulations of Winick and co-workers [1968, 19701. Since oligodendrocytes are the cells responsible for myelin synthesis, the present results also substantiate earlier findings on the decreased synthesis and content of myelin as a result of postnatal protein or calorie deficiency [Benton et al, 1966;Chase et al, 1967;Fishman et al, 1971;Nakhasi et al, 1975;Krigman and Hogan, 1976;Wiggins et al, 1976;Figlewicz et al, 1978;Kim and Pleasure, 19781. However, the present results are in disagreement with those of Bass et a1 [1970], who did not find any decrease in DNA content of the white matter region of rat brain in response to weanling undernutrition.…”
Section: Discussionsupporting
confidence: 93%
“…Here the literature data are divergent. For a weight loss in our range, brain myelin losses of 13.5% (Fishman et al, 1971), 75% at all ages (Wiggins et al, 1976), 16% (Reddy et al, 19791, 40% (Fuller et al, 1984), and 60-70% (Yeh, 1988) are reported. Blaker et al (1981) even report a stimulated myelin production in mild undernourishment from 16 to 30 days of age.…”
Section: Discussionmentioning
confidence: 68%
“…The effects on the oligodendroglia may be the primary ones, thus hampering the synthesis of the early myelin (15). As shown in table III the total amount of incorporated radioactivity into myelin seems to increase during a period of 40 days after the intracranial injection of labelled leucine.…”
Section: Discussionmentioning
confidence: 85%
“…At the end of the experiment (120 days after birth) this decrease reached 15 and 22% in group B and C, respectively, as compared to control, being of comparable severity to that induced by heavy undernutrition of rats for 1 -2 months after birth (15).…”
Section: Discussionmentioning
confidence: 89%